The influence of hydraulic fracture and reservoir parameters on the storage of CO2 and enhancing CH4 recovery in Yanchang formation - Kasala, Erasto E.; Wang, Jinjie; Lwazi, Hussein M.; Nyakilla, Edwin E.; Kibonye, John S. (Energy (Oxford), 2024)
The demand for a clean energy source from shale is growing day-to-day since it is not harmful to the environment like other fossil fuels. Further, shale reservoirs offer long-term geo-carbon dioxide (CO2) storage. Innovations in horizontal drilling and multi-stage hydraulic fracturing have made shale gas extraction and geo-CO2 storage economically viable. A three-dimensional Yanchang shale formation simulation model in Ordos's basin was developed using CMG-GEM, considering adsorption/desorption, diffusion, geomechanics, permeability changes, and non-Darcy flow. Two horizontally drilled wells, each 510 m long, were fractured and positioned 90 m apart. CO2 gas was injected into Well-2, producing methane (CH4) in Well-1. After simulation for 30 years, the cumulative mass of CH4 produced was 1.07×10+5kg, the cumulative mass of CO2 produced was 2.3×10+4kg, which is 1.14% of the mass injected, the cumulative mass of CO2 injected was 2.01×10+6kg and cumulative mass of CO2 gas stored was 1.987×10+6kg which is 98.86% of the injected mass of CO2 gas. The natural fracture system was the dominant factor of enhanced shale gas recovery and CO2 injection in the Yanchang shale formation. A sensitivity analysis was conducted with CMG-CMOST, examining the influence of reservoir and hydraulic fracture parameters in the storage of CO2 and enhancing CH4 recovery. Natural fracture porosity had the most significant impact on CH4 production and CO2 storage, followed by fracture permeability and half-length leading for hydraulic fracture parameters, with fracture conductivity being the least influential parameter. The approach used in this study applies to tight shale oil and gas formations in various sedimentary basins worldwide, enabling a more comprehensive understanding of reservoirs and hydraulic fracture parameters that can enhance oil and natural gas production. [Display omitted] •A multi-component adsorption model for assessing geo-CO2 storage and CH4 recovery was developed via CMG-GEM.•The model incorporates molecular diffusion, pressure-dependent permeability, non-darcy flow and geo mechanics comportments.•Petrophysical parameters and experimental fluid properties data assessed the efficiency of CO2 storage and CH4 recovery.•The model creates a better complex network for desorption of CH4 and the adsorption of CO2, reducing air pollution.•The study offers an improved solution for the energy sector.